Student’s halal awareness of dining at Korean restaurants - Azizan, Siti Aisyah Syafiqah; Ramlan, Nadiah (Universiti Teknologi MARA (UiTM), Malaysia, 2025)
Korean cuisine is fast gaining international acceptance, particularly among younger generations, since Korean pop culture has established itself as a media powerhouse. Muslim customers are not excluded from having a strong enthusiasm in and desire for Korean cuisine as it grows in popularity. The problem arises when some of the available Korean restaurants in Malaysia do not have halal certification from Jabatan Kemajuan Islam Malaysia (JAKIM), besides the issue of confusing Korean terms used for their menus. The aim of this research is to determine the factors affecting dining intention and to analyse the level of halal awareness of dining at Korean restaurants among students at the Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM) Shah Alam. This study adopted the quantitative method where the primary data were collected through 318 sets of survey questionnaire distributed to the target respondents. The data obtained were analysed using Statistical Package for the Social Sciences (SPSS) 28.0 to obtain the frequency, percentage, and mean of responses. From the findings, 68% respondents agreed that utilitarian value is the main factor that affects the intention of dining at Korean restaurants. Their level of halal awareness of dining at Korean restaurants is also high, where 78.9% of the respondents will avoid dining at Korean restaurants without a halal logo. In conclusion, the Muslims students from ACIS, UiTM Shah Alam are cautious about the halalness of the food they consume, particularly in Korean restaurants.